THE OVERVIEW OF GREEN TOBACCO SICKNESS AMONG TOBACCO FARMERS IN JEMBER DISTRICT, INDONESIA - Anita Dewi Prahastuti Sujoso; Tri Martiana; Santi Martini (Jurnal Berkala Epidemiologi, 2020)
Background: Green tobacco sickness (GTS) is a type of disease that is still not widely understood, but is often experienced by tobacco farmers. The duration and frequency of contact, the work procedures associated with wet tobacco, and individual vulnerability are risk factors for GTS. Purpose: This study aimed to measure the factors associated with incidences of GTS in tobacco farmers in Jember, Indonesia, to contribute to the prevention of GTS. Method: The research design used case-control. This research was conducted in Jember District, within a group of tobacco farmers. The case group included farmers who experienced GTS and the control group included farmers who did not experience GTS. The study measured age, sex, nutritional status, passive smoking status, alcohol consumption status, subjective complaints, individual hygiene, Occupational Health and Safety (OHS) attitudes, OHS actions, use of personal protective equipment, principal occupation, extra work, type of tobacco leaf, length of service, length of work-rest period, and workload. The study population were tobacco farmers. The sample size was determined using the Lemeshow sampling formula for case-control. The sampling technique was simple random sampling. Data analysis was conducted using chi-squared tests. Results: Variables related to GTS cases in tobacco farmers were sex (p = 0.01) and nutritional status (p = 0.03). There were no significant occupational factors. Conclusion: Factors that influence GTS are sex and nutritional status.